Effective Learning Spaces in Public Secondary Schools in Nigeria: A Study on The Impact of Students’ Engagement and Achievement - Olaseni, Vivian Morenike (Journal of Cultural Analysis and Social Change, 2026)
This research investigates the effectiveness of well-designed learning spaces on students' academic performance and engagement in public secondary schools in Nigeria. The review of previous studies showed that Nigerian public schools frequently struggle with structural issues, including overcrowded classrooms, inadequate ventilation, and disorganised spaces. The study employed a quasi-experimental research approach. The target population comprised all public secondary schools in Ondo State. A purposive sampling technique was employed to select two public secondary schools with distinct classroom settings. A general science subject Achievement Test and structured questionnaires were administered as part of the technique to gauge student performance and participation. Data were collected and analysed to compare students' results in classrooms with and without sufficient facilitation. The two groups' levels of engagement and academic performance differed significantly. On the General Science Subject Achievement Test, students in well-designed classrooms scored an average of 76.4, while those in poorly supported environments scored an average of 58.2, resulting in an 18.2-point difference. On a 3-point Likert scale, the well-facilitated group's average engagement score was 2.68, which appears significantly higher than the poorly facilitated group's score of 1.87. These differences were statistically significant across behavioural, emotional, and cognitive involvement (p < 0.05), as determined by independent t-tests. A visible difference in ventilation, lighting, furniture quality, and spatial arrangement was illustrated through visual representations and compared using bar charts. These elements were found to be significant predictors of both accomplishment and engagement. Based on the findings, the study therefore recommends using affordable, contextually relevant design elements to create accessible and engaging learning environments, such as improved lighting, ergonomic furnishings, and adjustable chairs. The study concludes that enhancing the physical learning environment is essential for attaining academic excellence and educational equity in public secondary schools in Nigeria.